Mengkaji Urgensi dan Tantangan Guru dalam Pengelolaan Kelas di Madrasah Ibtidaiyah pada Era Digital - Hilda Wahyuni; Triyo Supriyatno; Bintoro Widodo (Jurnal Ilmiah Profesi Pendidikan, 2025)
This research aims to examine the urgency and challenges faced by Madrasah Ibtidaiyah teachers in classroom management in the digital era. With the rapid development of technology, teachers are required to utilize it to enhance the effectiveness of learning. This study employs a descriptive qualitative method with a phenomenological approach, focusing on five teachers who have a minimum of one year of teaching experience and have utilized technology for classroom management. We collected data through semi-structured online interviews. The research results show that the use of technology has become an important necessity, but teachers face challenges such as limited infrastructure, lack of training, and moral dilemmas in maintaining Islamic principles. We can overcome this challenge by selecting appropriate technology, enhancing Islamic character education, providing teachers with technology training, and collaborating with parents.